Cerumen Impaction: Its Associated Risk Factors and Clinical Presentation (Medical Forum Monthly, 2022)
Objective: To determine the factors associated with cerumen impaction to endorse public education about safe ear hygiene, moreover encourage earlier detection and management at the healthcare professional’s level.Study Design: Prospective studyPlace and Duration of Study: This study was conducted at the ENT Department, Niazi Welfare Teaching Hospital, Sargodha, from January 2022 to July 2022.Materials and Methods: All the patients aged ≥15 years presented in the E.N.T clinic, diagnosed with cerumen impaction, were included. A detailed history was asked and ear examination was done. Patients with co-existing ear infections and patients not willing to participate were excluded. Statistical analysis was done on SPSS version 25.Results: A total of 539 patients who participated in our study, aged between 15 to 80 years (32.47± 16.21), showed male preponderances. Bilateral impaction (63.6%) was more prevalent. The narrow ear canal was the most common (34.7%) anatomical variation. The habit of inserting cotton-tipped swabs into ears was found among 80.5% of patients. The common complaints were ear blockage (97%), itching (72.9%), pain (31.7%), and tinnitus (31.4%).Conclusion: Impacted cerumen is associated with highly preventable risk factors. Public education about safe ear hygiene and timely referral of patients in ENT clinics will decrease the burden on the healthcare budget.